Impact of Head Tilt on Optical Coherence Tomography Image Orientation. Issue 12 (December 2018) - Mohammad, Syed; Jarrar, Faisal S.; Torres, Lucas A.; Sharpe, Glen P.; Vianna, Jayme R.; Chauhan, Balwantray C.
Abstract : Purpose: Head tilt can have an impact on the orientation of posterior pole images. We conducted this study to determine the effect of head tilt on image orientation measured by the fovea-Bruch's membrane opening (FoBMO) angle with optical coherence tomography (OCT) imaging. Methods: The study included 56 healthy subjects with mean (range) age of 33 (18 to 61) years. The dominant eye was first determined. To measure head tilt, a smartphone with a built-in gyroscope was affixed to the subject's head with adjustable straps. OCT imaging was performed in both eyes (in randomized order) at 0, 5, and 10 degrees of head tilt in the direction of the imaged eye (ipsilateral head tilt), and then in the opposite direction (contralateral head tilt). For each image, the device software determined Bruch's membrane opening center and the foveal pit from which the FoBMO angle was derived. Results: Thirty-eight (68%) subjects were right eye dominant and 18 (32%) were left eye dominant. Each 1 degree head tilt resulted in a mean change of 0.76 degree in the FoBMO angle ( P <0.01), with no significant difference in effect between the 2 eyes ( P =0.72). The magnitude of the effect increased from 5 to 10 degrees, and was similar for both ipsilateral and contralateral head tilt. Ocular dominance did not modulate the effect of head tilt ( P =0.42). Conclusions: Head tilt significantly affects OCT image orientation as measured by the FoBMO angle, presumably because cyclotorsion is not fully compensatory. The magnitude and direction of the effect does not depend on the dominant eye.